New technologies and productivity growth in the euro area - Ronald Albers; Focco Vijselaar (European Central Bank (ECB), 2002)
This paper provides an overview of the currently available evidence on the importance of information and communication technologies (ICT) for developments in productivity growth in the euro area. On the basis of the available data, there is evidence of an increased contribution of ICT to economic growth both in terms of production and investment in the second half of the 1990s. However, there is little, if any, evidence of significant positive spillover effects from the use of ICT to overall productivity growth. This implies that there is no reason to believe that potential output growth in the euro area has increased significantly in recent years on account of new technologies
Keywords: E22; L63; L86; O3; O47; 330; average labour productivity; capital stock; euro area; growth accounting; Information and communication technologies; measurement issues; sectoral developments